PWE-292 How many cases does it take to learn how to do trus?. (22nd June 2015) - Hoh, CSL; Pickering, G; Hampton, J; Vinayagam, R; Smith, L; Brown, S
Abstract : Introduction: Three dimensional transrectal endosonography (3D TRUS) is a very sensitive technique for preoperative staging of early rectal cancer and is recommended as an adjunct for these patients to optimise therapy. Major limitations include complexity of interpretation and operator variability. A learning curve definitely exists. If a centre wants to establish a service, how many cases do they need to do before they can reliably interpret the scans? A cumulative sum (CUSUM) analysis provides a simple and practical tool for monitoring cumulative performance. Method: This is a descriptive single-centre study using routinely collected clinical data from 233 patients who were diagnosed of early rectal cancer between 1 Jan 2008 to 31 Dec 2014. 3D TRUS was performed to identify the pre-operative T staging of the tumour. This was compared to post-surgical pathological T staging of the lesion. A CUSUM analysis chart based on sequential monitoring of cumulative performance was used for evaluating the learning curve for 3D TRUS. Results: Two hundred and thirty three patients (153 male) had 3D TRUS over the six years. 172 (73.8%) were available for analysis (52 did not have post-surgical histology for comparison and 9 could not be staged). Overall accuracy of T staging was 75%. The CUSUM analysis demonstrated a learning curve of 31 cases to reach a level of steady state performance. Conclusion: These data provide some insight into the number of cases required to achieve an acceptable accuracy if a TRUS service is to be established in a hospital or region. Disclosure of interest: None Declared.